Shari’ah Compliances Stock Market Integration: Evidence From Indonesia and Malaysia - Helma Malini (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The nature of stock market integration has been an issue for almost a decade; this issue is more complicated toward Shari’ah compliance between countries since there are differences of companies screening process that can be classified as Shari’ah compliances. The differences make the integration of Shari’ah compliances stock market become a major issue in trying to answer the question whether one country can be the placed for Shari’ah portfolio diversification. This study aims to measure Shari’ah compliances integration and portfolio diversification in Indonesia and Malaysia Shari’ah compliances toward other Shari’ah compliances in the world. Six Shari’ah compliances are selected based on countries level of development and geographical factor. This studies relies on two major time series investigation techniques, namely the Auto-Regressive Distributed Lag (ARDL) approach and multi-variate Vector Error Correction Mechanism (VECM), based on the Generalized Methods of Moments (GMM). The ARDL approach is used to determine the existence of long run integration among Shari’ah compliances, while the multi-variate VECM based on the GMM is adopted to provide a robust analysis of short and long-run dynamic causal linkages among the stock markets.Keywords: Efficient Market Hypothesis, Portfolio Diversification, Shari’ah compliances Integration